Efficiency assessment of a novel automatic mosquito pupae sex separation system in support of area-wide male-based release strategies - Mamai, W; Bueno-Masso, O; Wallner, Markus; Nikièma, S A; Meletiou, Sotiris; Deng, L; Balestrino, F; Yamada, H; Bouyer, J (My University, 2024)
This study provides a comparative analysis of two state-of-the-art automatic mosquito pupae sex sorters currently available: the ORINNO and the WOLBAKI Biotech pupae sex separation systems, which both exploit the sexual size dimorphism of pupae. In Aedes aegypti, the WOLBAKI sex sorter and the ORINNO with a sieve mesh size of 1.050 mm achieved sex separation with female contamination rates below 1%, low pupae mortality rates and high male flight capacity. However, in Ae. albopictus, there was more variability, with female contamination rates above the 1% threshold and pupae mortality reaching 27% when using the ORINNO sorter. On the other hand, the WOLBAKI sorter achieved a male pupae recovery of 47.99 ± 8.81% and 50.91 ± 11.77% in Ae. aegypti and Ae. albopictus, respectively, while the ORINNO sorter with a smaller sieve size achieved male pupae recoveries of 38.08 ± 9.69% and 40.16 ± 2.73% in Ae. aegypti and Ae. albopictus, respectively. This study provides valuable information for researchers and practitioners in the field, assisting in the selection of the most suitable system for mosquito control, management and research programs depending on their specific requirements.